Pembrolizumab Plus Axitinib Versus Sunitinib as First-line Treatment of Advanced Renal Cell Carcinoma: 43-month Follow-up of the Phase 3 KEYNOTE-426 Study - Plimack, Elizabeth R; Powles, Thomas; Stus, Viktor; Gafanov, Rustem; Nosov, Dmitry; Waddell, Tom; Alekseev, Boris; Pouliot, Frédéric; Melichar, Bohuslav; Soulières, Denis; Borchiellini, Delphine; McDermott, Raymond S; et al. (European urology, 2023)
Previous analyses of KEYNOTE-426, an open-label, phase 3 randomized study, showed superior efficacy of first-line pembrolizumab plus axitinib to sunitinib in advanced clear cell renal cell carcinoma (ccRCC). We report results of the final protocol-prespecified analysis of KEYNOTE-426. Patients received pembrolizumab 200 mg intravenously every 3 wk plus axitinib 5 mg orally twice daily or sunitinib 50 mg orally once daily (4 wk per 6-wk cycle). The dual primary endpoints were overall survival (OS) and progression-free survival (PFS) as per RECIST v1.1 by a blinded independent central review. The secondary endpoints included objective response rate (ORR) and duration of response (DOR). The median study follow-up was 43 (range, 36-51) mo. Benefit with pembrolizumab plus axitinib versus sunitinib was maintained for OS (hazard ratio [HR], 0.73 [95% confidence interval CI, 0.60-0.88]), PFS (HR, 0.68 [95% CI, 0.58-0.80]), and ORR (60% vs 40%). The median DOR was 24 (range, 1.4+ to 43+) versus 15 (range, 2.3-43+) mo in the pembrolizumab plus axitinib versus the sunitinib arm. No new safety signals emerged. These results support pembrolizumab plus axitinib as a standard of care for patients with previously untreated advanced ccRCC. PATIENT SUMMARY: Extended results of KEYNOTE-426 support pembrolizumab plus axitinib as the standard of care for advanced clear cell renal cell carcinoma.
Keywords: následné studie; Axitinib; axitinib; Antineoplastic Combined Chemotherapy Protocols; Immunotherapy; Carcinoma, Renal Cell; protokoly protinádorové kombinované chemoterapie; nádory ledvin; Sunitinib; karcinom z renálních buněk; Humans; Renal cell carcinoma; sunitinib; Pembrolizumab; Kidney Neoplasms; Follow-Up Studies; lidé